2014
DOI: 10.3851/imp2661
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Myosin Light Chain Kinase Can be Targeted for the Development of New Therapies against Herpes Simplex Virus Type-1 Infection

Abstract: We provide new evidence that NM-IIA and MLCK can be used as effective antiviral targets against ocular herpes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 48 publications
3
17
0
Order By: Relevance
“…Herpes simplex virus type 1 (HSV-1) is a world-spread pathogen which infects over a half of adult humans, resulting in diverse ocular, oral, and genital manifestations (Antoine and Shukla, 2014; Lathe and Haas, 2016). Currently, we still have no effective means for treating HSV-1.…”
Section: Nm II In Microbial-triggered Discordsmentioning
confidence: 99%
See 3 more Smart Citations
“…Herpes simplex virus type 1 (HSV-1) is a world-spread pathogen which infects over a half of adult humans, resulting in diverse ocular, oral, and genital manifestations (Antoine and Shukla, 2014; Lathe and Haas, 2016). Currently, we still have no effective means for treating HSV-1.…”
Section: Nm II In Microbial-triggered Discordsmentioning
confidence: 99%
“…Moreover, treatment of the murine model with ML-7 before viral inoculation could significantly inhibit HSV-1 infection and improve survival rate. Therefore, both ML-7 and ML-9 are used as novel therapies to block HSV-1 infection by inhibiting MLCK activity (Antoine and Shukla, 2014).…”
Section: Nm II Inhibitors With Potential Drug Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study designed synthetic peptides specific to the glycoproteins gD and gG and showed that these peptides can effectively recognize HSV-2 antibodies and hence may be used for serodiagnostic assays 132 . Because HSV utilizes the cytoskeleton filaments and kinases during its entry, a recent study showed that blocking the myosin light chain kinase (MLCK) with inhibitors such as blebbistatin significantly reduces HSV infection 133 , providing new evidence for potential targets in blocking HSV infections. The advent of nanoparticles in drug delivery was successful, owing to their ability to provide sustained or extended delivery of drugs at a local site.…”
Section: Treatment and Preventionmentioning
confidence: 99%